APHORISMS IN ENGLISH AND UZBEK, EXPRESSING LOVE FOR MOTHER - Jo’raqulova Hurmatoy (TADQIQOTLAR, 2025)
Annotation: This article explores the thematic and cultural significance of aphorisms that express motherly love in Uzbek and English traditions. Using a comparative literary approach, the study analyzes selected aphorisms, proverbs, and quotations from both cultures. The findings reveal that maternal love is universally portrayed as unconditional, eternal, and protective. However, Uzbek aphorisms emphasize the sacred and spiritual role of the mother, often linking her blessing to divine approval, while English aphorisms highlight her emotional and motivational influence on personal growth and achievement. The article concludes that, despite cultural variations, the image of the mother remains a timeless symbol of compassion, sacrifice, and guidance in human life.